Digital communication strategies of lobbies in the European Union - Emilia Smolak Lozano (Frontiers in Political Science, 2025)
Digital technologies have made it easier for lobbies to reach a larger audience, generate support, and collect data to bolster their campaigns. At the same time, digital tools have contributed to increasing participation in lobbying activities, as information is more readily accessible to the public. Policymakers are also leveraging digital technologies to engage with a broader range of stakeholders, gather input on policy issues, and enhance transparency in the policymaking process. Lobbies, or interest groups, use digital tools and platforms to interact with policymakers, communicate their interests, and influence decision-making. However, there are concerns about the influence of big tech companies and the potential for digital lobbying to distort public policy outcomes. Overall, the digital age has reshaped the dynamics between lobbies and public policies, presenting both opportunities and challenges for achieving transparent and accountable governance. Currently, the EU lacks an evaluation or regulatory service to scrutinize digital lobbying strategies. In this digital age, the relationship between lobbyists and public policies has changed significantly, with technology playing a critical role. Although the EU Transparency Register attempts to improve transparency and accountability in interactions between interest groups and EU institutions, further development is needed in examining the digital discourse strategies of interest groups. The purpose of this study is to examine the digital strategies of lobbies in the EU through web mining, social media tracking, and text mining techniques. Content analysis will be conducted to identify and describe the digital strategies that EU lobbyists employ: online media, social media, online formats, and publications to advocate for and influence public policies. The results will reveal the strategies of lobby influence in digital environments and the scope and scale of the digital discourse created by these activities. This will provide deeper insights into the impact of these organizations on public policies in the EU across various sectors in terms of digital communication and the online factors influencing the policymaking process with engaged stakeholders. Finally, the methodology serves as a proposal for an analytical framework for monitoring the development of political communication by these entities with their stakeholders in the digital ecosystem and the resulting digital discourse.